The Indian social sphere : institutions and social transformations - Somayaji, Sakarama; Somayaji, Ganesha; Coelho, Joanna P. (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book studies the social formation of India through the lens of religion, state, ethnicity, and governance. It provides a nuanced understanding of the structural as well as the processual aspects of the Indian social sphere. The volume studies diverse themes, such as the impact of religiosity on religious consciousness, the primacy of tribal identity in colonial India, political inclusion of marginalised communities, the emerging subaltern activism, among others. An important contribution, this book will be of interest to scholars and researchers of sociology, political sociology, South Asian studies, Affirmative action, and political science"--
Keywords: Social change -- India; India -- Social conditions; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General